1986
DOI: 10.1021/bi00349a027
|View full text |Cite
|
Sign up to set email alerts
|

Identifying regions of membrane proteins in contact with phospholipid head groups: covalent attachment of a new class of aldehyde lipid labels to cytochrome c oxidase

Abstract: A series of amine-specific reagents based on the benzaldehyde reactive group have been synthesized, characterized, and used to study beef heart cytochrome c oxidase reconstituted in phospholipid bilayers. The series contained three classes of reagents: lipid-soluble phosphodiesters having a single hydrocarbon chain, phospholipid analogues, and a water-soluble benzaldehyde. All reagents were either radiolabeled or spin-labeled or both. The Schiff bases formed by these benzaldehydes with amines were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In these instances, the reaction products are stabilized by secondary reactions, although the structures have not been completely established in all instances. The simple aliphatic aldehydes yield Schiff bases that are more easily dissociated than those of the bifunctional aldehydes and require chemical reduction for stabilization (12,25).…”
Section: Discussionmentioning
confidence: 99%
“…In these instances, the reaction products are stabilized by secondary reactions, although the structures have not been completely established in all instances. The simple aliphatic aldehydes yield Schiff bases that are more easily dissociated than those of the bifunctional aldehydes and require chemical reduction for stabilization (12,25).…”
Section: Discussionmentioning
confidence: 99%
“…The latter may be of functional significance in the inner mitochondrial membrane, since cardiolipin is found to be an efficient activator of cytochrome oxidase ( [7,8] indicate that the source of the selectivity is not in al1 cases solely electrostatic. Covalent modification has indicated that lysine residues are involved in the lipid selectivity of cytochrome oxidase [ 131, and the subunits bearing some of the lysine groups involved have been identified [15]. The polar region (residues 116-150) that makes a major contribu-tion to the lipid selectivity of the myelin proteolipid protein has been located with the help of the DM-20 proteolipid mutant which lacks this portion of the sequence [la.…”
Section: Lipid-protein Associationsmentioning
confidence: 99%
“…When detergent-dissolved cytochrome c oxidase was reacted with [35S]-NAP-taurine, there was heavy labeling of Va but no labeling of Vb (results not shown). A set of experiments were also conducted with a second membrane-impermeant reagent methyl 4-[3H] formylphenyl phosphate (MFPP), which reacts to form a Schiff base with lysine residues in the presence of borohydride (McMillen et al, 1986). Analysis of enzyme labeled with MFPP in reconstituted vesicles and in detergent-dispersed form showed similar results to those with NAP-taurine: subunit Va was labeled in intact vesicles ( Figure 3A), detergent disruption of these vesicles gave only a small amount of additional labeling of this subunit, while Vb was not labeled even in detergent-solubilized cytochrome c oxidase (result not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Sodium methyl 4-[3H]formylphenyl phosphate (MFF'P) (5.5 mCi/mmol) was synthesized according to the procedure of McMillen et al (1986). MFPP was placed in a glass vial and solvent removed under nitrogen for 15 min.…”
Section: Covalent Labeling Of Detergent-solubilized and Membranous Cymentioning
confidence: 99%